2003
DOI: 10.1055/s-2003-39231
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Triiodothyronine on Human Osteoblast-Like Cells Metabolism and Interactions with Growth Hormone

Abstract: The expression of thyroid hormones receptors in osteoblasts and osteoclasts has involved these cells as direct targets for triiodothyronine (T3), but thyroid hormones may also interact with other hormones or local growth factors to exert their actions on bone cells. Among these, growth hormone (GH) is recognised as participating in the acquisition and maintenance of bone mass and exerting stimulatory effects on human osteoblastic cells. The aim of this study was to investigate T3 effects on primary human adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…61 It is likely that the thickness and percentage increase of trabecular bone in the offspring of rats treated with thyroxine may be due to increased osteogenic differentiation of stem cells promoted by thyroid hormones as demonstrated in vitro and in vivo . 13,62,63 So the increased bone apposition can also be explained by the direct influence of T 3 and T 4 on osteoblasts by stimulating the expression of proteins that are important for bone apposition, such as collagen X, alkaline phosphatase, 64 and osteocalcin. 65 In this study, excess thyroid hormone during pregnancy and lactation decreased VEGF expression in chondrocytes as shown by immunohistochemical and molecular analyses.…”
Section: Discussionmentioning
confidence: 99%
“…61 It is likely that the thickness and percentage increase of trabecular bone in the offspring of rats treated with thyroxine may be due to increased osteogenic differentiation of stem cells promoted by thyroid hormones as demonstrated in vitro and in vivo . 13,62,63 So the increased bone apposition can also be explained by the direct influence of T 3 and T 4 on osteoblasts by stimulating the expression of proteins that are important for bone apposition, such as collagen X, alkaline phosphatase, 64 and osteocalcin. 65 In this study, excess thyroid hormone during pregnancy and lactation decreased VEGF expression in chondrocytes as shown by immunohistochemical and molecular analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone directly stimulates osteoblast production of alkaline phosphatase [43,44], osteocalcin [24,45,46], osteoprotegerin [47], IGF-I [23], FGF receptor-1 [29], and matrix metalloproteinases [48,49]. These effects can be modulated by vitamin D and growth hormone [46,47,50,51].…”
Section: Thyroid Hormone and Skeletal Metabolismmentioning
confidence: 99%
“…In a randomized, double-blind, placebocontrolled trial that enrolled 389 postmenopausal women with osteopenia, it was shown that genistein enhanced BMD by increasing urinary excretion of pyridinoline and deoxypyridinoline and increasing alkaline phosphatase and serum insulin-like growth factor (IGF)-1 levels (Marini et al, 2007). Apart from the systemic circulation, IGF-1 is abundantly found in both trabecular and cortical bone (Pepene et al, 2004a,b) to directly or indirectly mediate the effects of estrogens, parathyroid hormone, growth hormone and thyroid hormones (Pepene et al, 2001(Pepene et al, , 2003 and glucocorticoids (Pepene et al, 2010) on bone cells metabolism. To support isoflavones positive effects on bone via the IGF-1/IGF-1R pathway, it was reported that isoflavones extracted from Sophorae fructus, (Isocal ® ) are able to up-regulate the growth factors IGF-1 and transforming growth factor-ß in rat bone marrow cells (Joo et al, 2004).…”
Section: Isoflavonesmentioning
confidence: 99%